(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Stalking is described as the act of following and harassing a woman or girl in public, potentially leading to verbal or physical assault. This study explores the potential of Twitter, Facebook, and Instagram in enhancing the sense of safety for women in major cities across India. It also investigates ways to encourage ordinary Indians to develop a sense of social responsibility, crucial for protecting women in their daily lives. Utilizing tweets, which typically combine images and text, could serve to educate Indian youth about the importance of promptly addressing harassment against women in urban areas. Twitter, along with other handles featuring hashtag messages widely circulated globally, offers a platform for women to share their perspectives on how they feel during commutes or while traveling in public transportation, their experiences with unfamiliar men, and whether they perceive their surroundings as secure. These messages are disseminated worldwide